Social Media Activism: The Rise of Digital Movements in the Global South - Pardomuan Pardosi; Hakim Muttaqim; Irwin Sukrisno Sugeng (Yayasan Adra Karima Hubbi, 2024)
The proliferation of social media has revolutionized activism, particularly in Global South countries, where traditional forms of protest often face significant constraints. This research examines the rise of digital movements facilitated by social media platforms, focusing on how these tools empower marginalized communities and amplify their voices. The study aims to analyze the strategies employed by activists and the impact of social media on mobilization and advocacy efforts in these regions. A mixed-methods approach was utilized, combining quantitative surveys of social media users involved in activism with qualitative interviews of key activists and organizations. Data were collected from several Global South countries to provide a comprehensive understanding of the digital activism landscape. Findings indicate that social media not only enhances the visibility of social issues but also fosters community building and solidarity among diverse groups. Activists reported increased engagement and reach through digital platforms, which have allowed them to bypass traditional media gatekeepers. The research concludes that social media plays a pivotal role in the resurgence of activism in the Global South, enabling grassroots movements to flourish. While digital tools offer unprecedented opportunities for mobilization, challenges such as misinformation and state repression remain prevalent. This study highlights the need for ongoing research into the dynamics of digital activism, particularly in understanding how social media can be leveraged to sustain movements and promote social change in the Global South. The insights gained contribute to the broader discourse on the evolving nature of activism in the digital era.